(untitled) (Journal of the College of Basic Education, 2022)
Learning mathematics is a problem identified by many researchers, educators, teachers and students themselves for all academic levels, such as the study (Bottag 1993) globally, the study (Al-Karsh 1998), the study (Abu Amira 2000) in the Arab world, the study (Bushra 1998), the study (Abdul Hussein 1998) and (Al-Saadi 2002). locally.